2020
DOI: 10.3390/ijms21020391
|View full text |Cite
|
Sign up to set email alerts
|

No Cytotoxic and Inflammatory Effects of Empagliflozin and Dapagliflozin on Primary Renal Proximal Tubular Epithelial Cells under Diabetic Conditions In Vitro

Abstract: Gliflozins are inhibitors of the renal proximal tubular sodium-glucose co-transporter-2 (SGLT-2), that inhibit reabsorption of urinary glucose and they are able to reduce hyperglycemia in patients with type 2 diabetes. A renoprotective function of gliflozins has been proven in diabetic nephropathy, but harmful side effects on the kidney have also been described. In the current project, primary highly purified human renal proximal tubular epithelial cells (PTCs) have been shown to express functional SGLT-2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Other potential advantages from SGLT2 inhibitors may be reduction of anti-inflammatory, anti-oxidant, and anti-fibrotic markers [ 94 ]. In addition, studies with Ipragliflozin, Dapagliflozin, and Empagliflozin found decreased levels for oxidative stress and macrophages markers (MCP-1, NF-kB, 8-OhdG, L-fatty acid, interleukin-6, monocyte-attractive-protein-1) [ 95 , 96 , 97 ]. Regarding adverse effects, the most commonly observed were genital infections, urinary tract infections, bone fractures, or diabetic ketoacidosis [ 89 , 98 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…Other potential advantages from SGLT2 inhibitors may be reduction of anti-inflammatory, anti-oxidant, and anti-fibrotic markers [ 94 ]. In addition, studies with Ipragliflozin, Dapagliflozin, and Empagliflozin found decreased levels for oxidative stress and macrophages markers (MCP-1, NF-kB, 8-OhdG, L-fatty acid, interleukin-6, monocyte-attractive-protein-1) [ 95 , 96 , 97 ]. Regarding adverse effects, the most commonly observed were genital infections, urinary tract infections, bone fractures, or diabetic ketoacidosis [ 89 , 98 ].…”
Section: Available Treatment Option For Lowering Uric Acidmentioning
confidence: 99%
“…Therefore, the development of novel therapies to improve renal regeneration capacity after AKI, to preserve renal function, and to prevent AKI is urgently needed. In this context, we wanted to offer a forum for the publication of new results on renal inflammation, injury and regeneration, as well as for the review and discussion of existing studies from this interesting research field.This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1-3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7-9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22].…”
mentioning
confidence: 99%
“…Kidney injury leading to focal segmental glomerulosclerosis was shown by variants in the collagen 4A5 gene, demonstrating that the molecular genetics of different players in the glomerular filtration barrier can be used to evaluate the causes of kidney injury [5]. In addition, another study suggested that renal disease in colitis mice might be associated with changes in glomerular collagens and glomerular filtration barrier-related proteins [4].No injury or inflammatory effects of two anti-diabetically used gliflozins on proximal tubular epithelial cells that were cultured in hyperglycemic conditions were found [10]. Stimulations with bacterial lipopolysaccharide were used to investigate acute renal fibrosis in a model of sepsis-induced Int.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its hypoglycemic effect is independent of islet function and insulin sensitivity [7]. Several studies have shown that DAPA inhibits the expression of SGLT2 in renal tubules and causes renal vascular remodeling, thereby exerting a protective effect on the kidneys [8].…”
Section: Introductionmentioning
confidence: 99%